2021
DOI: 10.1111/liv.15096
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns and outcomes associated with intravenous albumin in patients with cirrhosis and acute kidney injury

Abstract: Background & Aims: Guidelines recommend albumin as the plasma-expander of choice for acute kidney injury (AKI) in cirrhosis. However, the impact of these recommendations on patient outcomes remains unclear. We aimed to determine the practice-patterns and outcomes associated with albumin use in a large, nationwide-US cohort of hospitalized cirrhotics with AKI.Methods: A retrospective cohort study was performed in hospitalized cirrhotics with AKI using Cerner-Health-Facts database from January 2009 to March 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, the underutilization of albumin use provides a key area for quality improvement in the management of AKI in patients with cirrhosis. [20] Lastly, despite using validated ICD-9/10 codes that carry high sensitivity for the diagnosis of cirrhosis, the possibility for cirrhosis misclassification may exist. Despite the limitations of our study, there are also several strengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the underutilization of albumin use provides a key area for quality improvement in the management of AKI in patients with cirrhosis. [20] Lastly, despite using validated ICD-9/10 codes that carry high sensitivity for the diagnosis of cirrhosis, the possibility for cirrhosis misclassification may exist. Despite the limitations of our study, there are also several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with Huelin et al, 1 the AKI recovery rates for stage 1A in our study were similar (90% vs. 86.9%) and higher in stage 1B, 50% versus 68.9%. Nevertheless, the underutilization of albumin use provides a key area for quality improvement in the management of AKI in patients with cirrhosis 20 . Lastly, despite using validated ICD-9/10 codes that carry high sensitivity for the diagnosis of cirrhosis, the possibility for cirrhosis misclassification may exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluids should be administered to all patients with cirrhosis and AKI when hypovolemia is suspected, in accordance with the cause and severity of fluid loss 5,6 . A large recent retrospective analysis found that albumin infusion was not associated with superior outcomes in comparison with crystalloids for AKI in patients with cirrhosis 41 . However, in cases of stage 2 or greater AKI (increase in serum creatinine > 2-fold from baseline) of unclear etiology, consensus guidelines recommend administering albumin at a dose of 1 g/kg for 2 days to distinguish HRS-AKI from other prerenal causes 5,6 …”
Section: Aki/hrsmentioning
confidence: 99%
“…[5,6] A large recent retrospective analysis found that albumin infusion was not associated with superior outcomes in comparison with crystalloids for AKI in patients with cirrhosis. [41] However, in cases of stage 2 or greater AKI (increase in serum creatinine > 2-fold from baseline) of unclear etiology, consensus guidelines recommend administering albumin at a dose of 1 g/kg for 2 days to distinguish HRS-AKI from other prerenal causes. [5,6] HYPONATREMIA Hyponatremia is very common among patients with cirrhosis and is associated with increased mortality.…”
Section: Intervention: Identification Of Precipitating Causementioning
confidence: 99%